2010
DOI: 10.1016/j.funbio.2010.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Multigene phylogenetic and population differentiation data confirm the existence of a cryptic species within Chrysoporthe cubensis

Abstract: Chrysoporthe cubensis is one of the most important pathogens of Eucalyptus. Based on phylogenetic evidence and geographic origin, isolates of this fungus are known to reside in distinct 'South America' and 'Southeast Asia' clades. In this study, reproductive isolation amongst these isolates of C. cubensis was tested using gene flow statistics for 12 polymorphic loci, and to support these data, phylogenetic affiliations based on gene trees and a multigene phylogeny were used. Gene flow statistics between popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 73 publications
1
40
0
1
Order By: Relevance
“…Breeding programs usually involve more than one intention, including breeding for quality, for yield, for different resistance to diseases, and other factors. That is why breeding lines can be a mixture of parental genotypes other than those classified into group C or E. A similar hidden genetic structure was found, for example, in the Chrysoporthe cubensis population (Van der Merwe et al 2010).…”
Section: Resultsmentioning
confidence: 56%
“…Breeding programs usually involve more than one intention, including breeding for quality, for yield, for different resistance to diseases, and other factors. That is why breeding lines can be a mixture of parental genotypes other than those classified into group C or E. A similar hidden genetic structure was found, for example, in the Chrysoporthe cubensis population (Van der Merwe et al 2010).…”
Section: Resultsmentioning
confidence: 56%
“…Bayesian analysis showed that chemotype 2 is polyphyletic and a genealogical concordance multigene analysis (e.g. Van der Merwe et al 2010;Lamprecht et al 2011) would be necessary to test the monophyly of this group and to elucidate its phylogenetic relations with strains of chemotype 1 and Diaporthe neotheicola, since ITS region alone may not be appropriate for species recognition within this group (Santos et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Cryphonectria parasitica has been isolated from Chinese chestnut (Castanea mollissima) on which it causes a mild canker and die-back disease (Fairchild, 1913;Shear & Stevens, 1913) and Cryphonectria nitschkei is known from cankers on Quercus (Fagaceae) (Teng, 1934;Myburg et al, 2004). Species of Chrysoporthe and Celoporthe are known from trees in the Myrtaceae and these include Chrysoporthe deuterocubensis from Eucalyptus and Syzygium cumini (Chen et al, 2010;Van der Merwe et al, 2010), Celoporthe syzygii from S. cumini, and Celoporthe eucalypti and Celoporthe guangdongensis from species of Eucalyptus (Chen et al, 2011). Inoculation tests have shown that all these species from the Myrtaceae are pathogenic to Eucalyptus and S. cumini (Chen et al, 2010(Chen et al, , 2011.…”
Section: Introductionmentioning
confidence: 99%